On some Types of coc-functions - Sattar Hameed Hamzah; Noor Hassan Kadhim (Al-Qadisiyah Journal of Pure Science, 2018)
In this work , we investigate the properties of product of some coc- functions namely coc- continuous ,coc-irresolute , strongly coc-closed and introduce the definition of coc-perfect, and investigate the properties of composition, restrictions and product of this type. Also, We give the relation among them.